2020
DOI: 10.1371/journal.pone.0229166
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of Hepatitis B, C and D in Germany: A scoping review

Abstract: BackgroundGermany is considered to be a low prevalence country for viral Hepatitis B, C and D (HBV, HCV, HDV). However, the burden of disease can be high among subpopulations. To meet the world Health Organization (WHO) viral hepatitis (VH) elimination goals, a national strategy was developed by the German government in 2016. We performed a scoping review to understand the baseline epidemiological situation in Germany regarding burden of disease, sequelae and care of HBV, HCV and HDV as a reference to monitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 79 publications
(21 reference statements)
1
13
0
2
Order By: Relevance
“…Attempts were made to compensate this by including non-published articles from the RKI Epidemiological Bulletin (EpiBull) and relevant regional journals. Moreover, a manual search was performed of reference lists in the included publications of the overall scoping review on VH epidemiology ( 6 ), and 14 references were identified but none were on prevalence. Further efforts, such as conducting a search for gray literature through other sources would potentially increase the number of relevant non-published literature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Attempts were made to compensate this by including non-published articles from the RKI Epidemiological Bulletin (EpiBull) and relevant regional journals. Moreover, a manual search was performed of reference lists in the included publications of the overall scoping review on VH epidemiology ( 6 ), and 14 references were identified but none were on prevalence. Further efforts, such as conducting a search for gray literature through other sources would potentially increase the number of relevant non-published literature.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis was part of a large comprehensive review covering all aspects of viral hepatitis B, D, and D epidemiology in Germany and presents data on VH prevalence until 2017 (6). With this comprehensive review, information on the baseline situation which is necessary for better monitoring of VH elimination in Germany was collected.…”
Section: Methodology-strengths and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…B. zur Inzidenz, MortalitĂ€t und zu SpĂ€tfolgen der Hepatitis B und C sowie zur sog. Behandlungskaskade [ 9 , 17 ]. Eine weitere Datenquelle ist die Nationale Kohorte, eine populationsbasierte deutsche Kohortenstudie, die eine Gesamtteilnehmerzahl von 200.000 Erwachsenen anstrebt.…”
Section: Introductionunclassified